Optimization of Liquid Organic Hydrogen Carrier (LOHC) dehydrogenation system - Rao, Nihal; Lele, Ashish K.; Patwardhan, Ashwin W. (International Journal of Hydrogen Energy, 2022)
In this paper, the perhydrodibenzyltoluene dehydrogenation flowsheet has been simulated. Modelling of the dehydrogenation reactor has been performed using the 1-D model. External and internal mass transfer resistances are also considered. Non-isothermal pellet condition has been considered for simulating the dehydrogenation reactor. The flowsheet simulation has been carried out in DW-Sim v 6.5.2 integrated with the reactor model coded in Python. NET. The dehydrogenation reactor is operated at a feed temperature between 523 K -613 K, a wall temperature of 623 K and 653 K, and a reactor pressure maintained at 1.2 atm. The amount of catalyst required for the perhydrodibenzyltoluene (PDBT) dehy-drogenation reactor is evaluated such that the conversion reaches 99%. The process flowsheet has been simulated to produce 10 Nm(3)/hr of industrial-grade hydrogen. The effects of feed temperature, wall temperature, and hydrogen burner efficiency on various system requirements, including catalyst weight, energy supplied to the dehydrogenation reactor, areas of the heat exchanger, and hydrogen production from the reactor, have been discussed. Preliminary cost optimization based on the heat exchangers and catalyst at various feed temperatures, reactor wall temperature, and hydrogen burner efficiency has been carried out. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Dehydrogenation; DWSim; LOHC; Perhydrodibenzyltoluene; Python; simulation